Taking the EU to Court - Adam, Christian. author. (orcid)0000-0002-1755-5243 Link aut Link
XXI, 239 p. 14 illus.
Keywords: This open access book provides an exhaustive picture of the role that annulment conflicts play in the EU multilevel system. Based on a rich dataset of annulment actions since the 1960s and a number of in-depth case studies, it explores the political dimension of annulment litigation, which has become an increasingly relevant judicial tool in the struggle over policy content and decision-making competences. The book covers the motivations of actors to turn policy conflicts into annulment actions, the emergence of multilevel actors’ litigant configurations, the impact of actors’ constellations on success in court, as well as the impact of annulment actions on the multilevel policy conflicts they originate from. Christian Adam is Assistant Professor at the Geschwister Scholl Institute for Political Science, Ludwig Maximilians Universität München, Germany. Michael W. Bauer holds the Jean Monnet Chair for Comparative Public Administration and Policy Analysisat the German University of Administrative Sciences Speyer. He is also a part-time professor at the School of Transnational Governance, European University Institute, Florence, Italy. Miriam Hartlapp is Professor of Comparative Politics: Germany and France at the Freie University Berlin, Germany. She previously held chairs at Leipzig (2014–17) and Bremen University (2013–14) and worked at the Max Planck Institute for the Study of Societies in Cologne. Emmanuelle Mathieu is Lecturer at the University of Lausanne, Switzerland. Previously, she was a Marie Curie research fellow at the Barcelona Institute for International Studies, Spain.